Treatment-resistant depression and major depression with suicide risk—The cost of illness and burden of disease - Sousa, Rute Dinis; Gouveia, Miguel; Nunes da Silva, Catarina; Rodrigues, Ana Maria; Cardoso, Graça; Antunes, Ana Filipa; Canhao, Helena; de Almeida, José Miguel Caldas (Frontiers in Public Health, 2022)
Introduction: Treatment-Resistant Depression (TRD) and Major Depression with Suicide Risk (MDSR) are types of depression with relevant effects on the health of the population and a potentially significant economic impact. This study estimates the burden of disease and the costs of illness attributed to Treatment-Resistant Depression and Major Depression with Suicide Risk in Portugal. Methods: The disease burden for adults was quantified in 2017 using the Disability-Adjusted Life Years (DALYs) lost. Direct costs related to the health care system and indirect costs were estimated for 2017, with indirect costs resulting from the reduction in productivity. Estimates were based on multiple sources of information, including the National Epidemiological Study on Mental Health, the Hospital Morbidity Database, data from the Portuguese National Statistics Institute on population and causes of death, official data on wages, statistics on the pharmaceutical market, and qualified opinions of experts. Results: The estimated prevalence of TRD, MDSR, and both types of depression combined was 79.4 thousand, 52.5 thousand, and 11.3 thousand patients, respectively. The disease burden (DALY) due to the disability generated by TRD alone, MDSR alone, and the joint prevalence was 25.2 thousand, 21 thousand, and 4.5 thousand respectively, totaling 50.7 thousand DALYs. The disease burden due to premature death by suicide was 15.6 thousand DALYs. The estimated total disease burden was 66.3 thousand DALYs. In 2017, the annual direct costs with TRD and MDSR were estimated at € 30.8 million, with the most important components being medical appointments and medication. The estimated indirect costs were much higher than the direct costs. Adding work productivity losses due to reduced employment, absenteeism, presenteeism, and premature death, a total cost of € 1.1 billion was obtained. Conclusions: Although TRD and MDSR represent relatively small direct costs for the health system, they have a relevant disease burden and extremely substantial productivity costs for the Portuguese economy and society, making TRD and MDSR priority areas for achieving health gains.